Sustainable Varieties of Capitalism? The Greening of Steel Work in Brazil and Germany - Doering, Heike; Evans, Claire; Stroud, Dean (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2015)
The aim of this article is to investigate the sustainability agenda and its implications for employment and managerial practices within different institutional contexts. The article uses the comparative capitalisms literature and, in particular, the Varieties of Capitalism framework to examine how multinational corporations (MNCs) can exploit different institutional contexts to achieve competitive advantages. We explore one multinational steel company’s i.e. SteelCo.AG varied responses to the emerging constraints of the sustainability agenda in Germany, as an example of a Coordinated Market Economy, and Brazil, as an example of a Hierarchical Market Economy. In particular, we focus on evidence concerning training, environmental practices and policies in the different company sites.We demonstrate how different institutional contexts favour different corporate strategies from an approach that exploits negative institutional complementarities, such as the “low-skill/low-cost trap,” to one that benefits from strong institutional coherence facilitating skills formation and innovation in response to environ-mental legislation. Our analysis argues for the importance of incorporating the green agenda as a marker of difference into the existing VoC framework. This allows for nuanced readings of unstable institutional complementarities in terms of operational, managerial and social innovation in different institutional contexts – with such analyses essential for understanding workers’ experiences of employment and work. Our contribution to the extant literature on the employment relationship, within the context of VoC analysis, therefore offers empirical material on understandings of employment relations within the HME category, as a new type within the VoC framework, through our discussion of a multinational’s activities in Brazil. This also allows us to focus on the way companies and other actors’ impact upon institutional frameworks and the distribution of power between different actors within particular contexts, thereby addressing recent discussions of the stability and homogeneity of institutional arrangements.